ROAD USERS’ BEHAVIOUR STUDY IN AREAS OF ZEBRA CROSSWALKS - Maria DĄBROWSKA-LORANC (Silesian University of Technology, 2021)
Pedestrian safety on crosswalks is extremely vital in Poland since 2015, when the first study on road users’ behaviour on driver–pedestrian encounters in areas of zebra crosswalks were conducted. The second study was carried out in 2018 and its results are published in this article for the first time. The results of the project helped lead to changes in pedestrians’ safety regulations in Poland, increasing the safety of pedestrians in areas of crossing. Since June, the 1st, 2021, drivers of oncoming cars approaching a zebra crossing are obliged to stop to allow pedestrians approaching from the sidewalk to cross the zebra crossing. Data to assess pedestrian safety presented in this article combine a new approach that is a combination of different diagnostic techniques: a surrogate safety measure (non- accident-based indicators) and the traditional approach: statistical analysis. As a result of the study, the most frequent categories of interactions between drivers and pedestrians and pedestrians itself were characterized on crossing facilities. Videos recording pedestrians’ and drivers’ behaviours, and vehicle speed measurements at pedestrian crossings from 2018 allow to assess the safety of 7 000 pedestrians during behaviour observation in on- site fields: on all crossing facilities, except with light signalization, 55% of pedestrians had to stop and wait at the sidewalks to cross, before an oncoming car. Only 45% of drivers approaching not signalised zebra crossings gave way to pedestrians. Pedestrians aged 60+ entering the road on marked crossings without traffic light waited longer to cross than younger. In residential areas with high traffic volume more drivers stopped at non signalised crossings and gave way to pedestrians. At low speed of vehicle in urban areas pedestrians felt safer and were ready to enter the crossing; their behaviour was more predictable. Results showed dangerous pedestrian behaviours on signal-regulated crossing facilities who failed to obey the traffic lights (7% of red-light crossings). 8% of observed pedestrians crossed the street outside designated pedestrian crossings. Video-recorded speed measurements of over 32 000 vehicles on-site study fields of pedestrian crossings showed that the speed of vehicles was higher than permitted. This article presents the newest characteristics of traffic and pedestrian’ behavior at crossings together with measurements of pedestrians’ speed and loss of pedestrians’ time on different road cross sections in Poland in 2018.